The Influence of Flash Sale, Cash Back, and Free Shipping on Decisions to Purchase Garnier Products on Shopee (Case Study of Garnier Users in Cirebon City) - Dewi Aulia Putri; Cita Mara; Andres; Rahmadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Nowadays, more and more SkinCare is emerging from countries around the world which then results in SkinCare trends. Various Skincare Brands have sprung up on the Shopee e-commerce site and one of them is the Garnier Skincare Brand. This study seeks to explore how the influence of Flash Sale, Cashback, Free Shipping on purchasing decisions for Garnier products at Shopee. This study uses quantitative data analysis methods using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. Primary data was collected by distributing questionnaires to 180 consumers who shop for garnier skincare using the Shopee application and live in Cirebon City. The results showed that flash sales had a significant effect on purchasing decisions with a T table value of 12.480 and a p value of 0.000, as well as cashback had a significant effect on purchasing decisions with a T table value of 6.020 and a p value of 0.000 and finally free shipping also had a significant effect on purchasing decisions with a T table value of 10.020 and a p value of 0.000.